Development of Guided-Inquiry-Based Buffer Solution E-Module - Ilahi, Rahayu Putri; Mawarnis, Elvy Rahmi; Herman, Mimi (Hydrogen: Jurnal Kependidikan Kimia, 2023)
This study aimed to evaluate the validity and practicality of a Guided Inquiry-Based Chemistry E-module for 11th-grade students at SMAN 1 Sijunjung. The study was conducted using a Research and Development (R&D) approach with the 4-D model (define, design, develop, and disseminate), and only the define, design, and develop stages were carried out. During the define stage, the learning conditions and instructional requirements were understood, while the design stage involved preparing the Chemistry E-module. In the develop stage, the validity and practicality of the E-module prototype were tested. The results of the study show that the Guided Inquiry-Based Chemistry E-module met standards with regard to its construction validity, as evidenced by a result of 94.4%. The module was also found to be highly practical based on student perception, with 86.4% of students indicating that the E-module was useful in the classroom. Overall, the findings suggest that the developed Guided Inquiry-Based Chemistry E-module can serve as an effective learning resource for students.